Econometric Approach to the Regional Integration Analysis - Nosova, Olga (Podejście ekonomiczne do analizy integracji regionalnej, 2010)
In Ukraine, an accounting database harmonized with statistics, aimed at all categories of users, had to be developed. A possibility to harmonize official accounting systems is stipulated by peculiar common characteristics: the use of monetary indexes; the use of economic categories in conceptual device; orientation at external information users; aggregation (consolidation, generalization) of received data; initiatives concerning constant increasing of quality of information. Related characteristics peculiar to accounting systems together with absence of conceptual contradictions between these systems allow to talk about possibility of harmonization of accounting information.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 115-120
Keywords: econometric approach; regional; integration; analysis